Exploring Knowledge Sharing, Retention, and Production in Indonesian Islamic Universities: A Case Study Approach - Fauzi Muharom; Yayan Andrian; Arina Hasbana (STAI Hubbulwathan Duri, 2024)
This study investigates the processes of knowledge sharing, retention, and production within Indonesian Islamic universities, employing a case study approach. The research prioritizes qualitative data collected through interviews, observations, and documentation studies. Data analysis involved descriptive methods based on events observed during field activities. Findings reveal that knowledge sharing among lecturers primarily revolves around interaction, communication, and the exchange of information, knowledge, and experiences both face-to-face and virtually. Policies at the faculty and program levels facilitate these activities, emphasizing the collaboration between senior and junior lecturers in research and community service. Knowledge production is inherently linked to knowledge sharing and retention, occurring organically within the university setting. However, the contribution and intervention of faculties and study programs remain limited. Enhanced involvement of faculties and programs in implementing knowledge management practices is essential for improving overall performance. Consequently, it is imperative for universities to adopt knowledge management as a foundational aspect of their operations.